PROBLEMATIKA PENGADAAN STANDAR OPERASIONAL PROSEDUR (SOP) DI KELOMPOK BERMAIN (KB) AL-IZZAH KECAMATAN SUKOLILOH KABUPATEN PATI-JAWA TENGAH - Sekar Fitri Aulia, Desi; Oktaviani, Ema; 'Izza, Khildatul; Hartanti, Dewy; Sintia Afika, Fahma; Ayu Pramudita, Diah; Fatimatuz Zahro, Siti; Nadiastuti, Intan (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2023)
The complete administration of project is needed in an institution or organization. There is a lot of administration in early childhood education institutions, especially in Study Groups. The purpose of this research is to find out what problems there are regarding the existence of SOP documents in the Al-Izzah KB. The method used in this research is qualitative. Data collection techniques use observation, documentation and interviews. The research results stated that the absence of SOP documents at KB Al-Izzah was due to a lack of quality educators and educational staff, and the regional coordinator was not comprehensive in monitoring and providing outreach at KB Al-Izzah regarding standard operational procedures. One of them is creating standard operating procedures. The SOP includes accepting new students, learning, developing the potential of educators and education staff, financing and involving parents/families, which are one of the requirements in building educational institutions.